Differential diagnosis of pulmonary sarcoidosis: a review - Valeyre, Dominique; Brauner, Michel; Bernaudin, Jean-François; Carbonnelle, Etienne; Duchemann, Boris; Rotenberg, Cécile; Berger, Ingrid; Martin, Antoine; Nunes, Hilario; Naccache, Jean-Marc; Jeny, Florence (Frontiers in Medicine, 2023)
Diagnosing pulmonary sarcoidosis raises challenges due to both the absence of a specific diagnostic criterion and the varied presentations capable of mimicking many other conditions. The aim of this review is to help non-sarcoidosis experts establish optimal differential-diagnosis strategies tailored to each situation. Alternative granulomatous diseases that must be ruled out include infections (notably tuberculosis, nontuberculous mycobacterial infections, and histoplasmosis), chronic beryllium disease, hypersensitivity pneumonitis, granulomatous talcosis, drug-induced granulomatosis (notably due to TNF-a antagonists, immune checkpoint inhibitors, targeted therapies, and interferons), immune deficiencies, genetic disorders (Blau syndrome), Crohn’s disease, granulomatosis with polyangiitis, eosinophilic granulomatosis with polyangiitis, and malignancy-associated granulomatosis. Ruling out lymphoproliferative disorders mau also be very challenging before obtaining typical biopsy specimen. The first step is an assessment of epidemiological factors, notably the incidence of sarcoidosis and of alternative diagnoses; exposure to risk factors (e.g., infectious, occupational, and environmental agents); and exposure to drugs taken for therapeutic or recreational purposes. The clinical history, physical examination and, above all, chest computed tomography indicate which differential diagnoses are most likely, thereby guiding the choice of subsequent investigations (e.g., microbiological investigations, lymphocyte proliferation tests with metals, autoantibody assays, and genetic tests). The goal is to rule out all diagnoses other than sarcoidosis that are consistent with the clinical situation. Chest computed tomography findings, from common to rare and from typical to atypical, are described for sarcoidosis and the alternatives. The pathology of granulomas and associated lesions is discussed and diagnostically helpful stains specified. In some patients, the definite diagnosis may require the continuous gathering of information during follow-up. Diseases that often closely mimic sarcoidosis include chronic beryllium disease and drug-induced granulomatosis. Tuberculosis rarely resembles sarcoidosis but is a leading differential diagnosis in regions of high tuberculosis endemicity.